Analog Circuit Design 2011
DOI: 10.1007/978-94-007-0391-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects and Hardening by Design in CMOS Technologies

Abstract: Radiation threatens the correct functionality of electronics in space, avionics, nuclear and High Energy Physics (HEP) applications. The engineering community involved in each of these disciplines has developed over time its specific set of solutions to ensure system reliability. The specificity is dictated by requirements in terms of cost, accessibility and mission criticality of each component/system. In some cases, the selection and use of Commercial-Off-The-Shelf components (COTS) represents the cheapest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…By analyzing the ENC curve, it can be concluded that the electronic devices can suffer from long-term radiation effects, and the effects are mostly due to electrons and protons [7]. Furthermore, this cumulative long term ionizing damage due to protons and electrons can cause devices to suffer threshold shifts, increased device leakage (and power consumption), timing changes, and decreased functionality [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…By analyzing the ENC curve, it can be concluded that the electronic devices can suffer from long-term radiation effects, and the effects are mostly due to electrons and protons [7]. Furthermore, this cumulative long term ionizing damage due to protons and electrons can cause devices to suffer threshold shifts, increased device leakage (and power consumption), timing changes, and decreased functionality [8,9].…”
Section: Resultsmentioning
confidence: 99%